Judaica Librarianship in the Age of the Internet - Weinberg, Bella (Judaica Librarianship, 1995)
What is the function of Judaica Librarianship, a printed journal, in the age of the Internet? This question has an underlying assumption: that paper journals will continue to exist in the electronic era. The question as well as the assumption are explored in this editorial.